Friendship’s Ontology. Giorgio Agamben-PÁvel Florenski - Mosto, Marisa (Tábano, 2020)
The essay draws bridges between the thinking of the Italian philosopher Giorgio Agamben and the Russian scientist, philosopher and theologian Pável Florenski around the theme of friendship. Both authors agree to give friendship a peculiar ontological status from which they derive categories of understanding that preach both anthropological, social, political, historical and messianic.